Modeling dysphonia severity as a function of roughness and breathiness ratings in the GRBAS scale - Ferrer, Carlos A.; Aragón, Efren; Hdez-Díaz, María E.; De Bodt, Marc S.; Cmejla, Roman; Englert, Marina; Behlau, Mara; Nöth, Elmar (Proceedings of the Annual Conference of the International Speech Communication Association, INTERSPEECH, 2021)
Dysphonia comprises many perceptually deviating aspects of voice, and its overall severity perception is made by the listener according to methods of aggregating the single dimensions which are personally conceived and not well studied. Roughness and breathiness are constituent dimensions in most devised rating scales in clinical use. In this paper, we evaluate several ways to model the mapping of the overall severity as a function of the particular ratings of roughness and breathiness. The models include the simple linear averaging as well as several non-linear variants suggested elsewhere, and some minor adjustments. The models are evaluated on four datasets from different countries, allowing a more global evaluation of how the mapping is conceived. Results show the limitations of the most widely assumed linear approach, while also hinting at a need for a more uniform coverage of the sample space in voice pathology datasets. The models explored in this paper can be expanded to higher-dimensional scales.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Breathiness; Dysphonia; Perceptual scales; Roughness; Vocal quality